A prospective, iterative, adaptive trial of carfilzomib‐based desensitization. Issue 2 (23rd October 2019) - Tremblay, Simon; Driscoll, James J.; Rike‐Shields, Adele; Hildeman, David A.; Alloway, Rita R.; Girnita, Alin L.; Brailey, Paul A.; Woodle, E. Steve
Abstract : Proteasome inhibitor–based strategies hold promise in transplant but have yielded varying results. Carfilzomib, a second‐generation proteasome inhibitor, may possess advantages over bortezomib, the first‐generation proteasome inhibitors. The purpose of this study was to evaluate the safety, toxicity, and preliminary efficacy of carfilzomib in highly HLA‐sensitized kidney transplant candidates. Renal transplant candidates received escalating doses of carfilzomib followed by plasmapheresis (group A) or an identical regimen with additional plasmapheresis once weekly before carfilzomib dosing. Thirteen participants received carfilzomib, which was well tolerated with most adverse events classified as low grade. The safety profile was similar to bortezomib desensitization; however, neurotoxicity was not observed with carfilzomib. Toxicity resulted in permanent dose reduction in 1 participant but caused no withdrawals or deaths. HLA antibodies were substantially reduced with carfilzomib alone, and median maximal immunodominant antibody reduction was 72.8% (69.8% for group A, P = .031, 80.1% for group B, P = .938). After depletion, rebound occurred rapidly and antibody levels returned to baseline between days 81 and 141. Bone marrow studies revealed that approximately 69.2% of plasma cells were depleted after carfilzomib monotherapy. Carfilzomib monotherapy–based desensitization provides an acceptable safety and toxicity profile while leading to significant bone marrow plasma cell depletion and anti‐HLA antibody reduction. Abstract : Carfilzomib‐based desensitization significantly depletes bone marrow plasma cells and reduces HLA antibodies with high tolerability and safety at doses of up to 36mg/m 2 twice weekly.